Electromechanical Impedance - Based Structural Health Monitoring Instrumentation System Applied to Aircraft Structures and Employing a Multiplexed Sensor Array - Isabela Iuriko Campos Maruo; Guilherme de Faria Giachero; Valder Steffen Junior; Roberto Mendes Finzi Neto (Journal of Aerospace Technology and Management, 2015)
The electromechanical impedance method has been seen as a promising tool for structural health monitoring regarding different types of structures and purposes. Most importantly, this method can be used in real-time applications. Frequently, massive, high-cost, single-channel impedance analyzers are used to process the time domain data, aiming at obtaining the complex, frequency-dependent electromechanical impedance functions and therefore infer about the presence, position and extent of an existing damage. However, for large structures, it is desirable to deploy an array of piezoelectric transducers over the area to be monitored and interrogate these transducers successively, in order to increase the probability of successful detection of damage at an early phase. The literature describes many miniaturized systems that can monitor large structures, however, presenting serious restrictions on data acquisition capabilities. This paper presents a hardware that is not limited to any data acquisition restriction, exhibiting an innovative way to measure the electromechanical impedance of multiplexed bonded transducers. Each logical block of the proposed architecture is presented in detail. The proposed system not only avoids costly fast Fourier transform analyzers/ algorithms, but also evades high-speed data acquisition hardware. A prototype using inexpensive integrated circuits and a digital signal processor was built and tested for two different types of structures: an aluminum beam and an aircraft aluminum panel. Simulated damages were introduced to each structure, and the detection performance of the prototype was tested. The actual prototype uses a universal serial bus connection to communicate with a personal computer.